2018
DOI: 10.1155/2018/5987973
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Estimation of Cracked Beams Based on Nonlinear Stress Distributions Near the Crack

Abstract: The crack presence causes nonlinear stress distributions along the sections of a beam, which change the neutral axis of the sections and further affect the beam stiffness. Thus, this paper presents a method for the stiffness estimation of cracked beams based on the stress distributions. First, regions whose stresses are affected by the crack are analyzed, and according to the distance to the crack, different nonlinear stress distributions are modeled for the effect regions. The inertia moments of section are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The increase in crack propagation towards the compressive block of cross-section causes the neutral line to change. Chunyu Fu et al (2018) [13] concluded that the presence of cracks causes a nonlinear stress distribution along the beam cross-section, which changes the neutral axis of the cross-section and further affects the stiffness of the beam. Figure 21 shows that the stiffness of the BRC beam cross-section decreases from the initial crack until the beam collapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in crack propagation towards the compressive block of cross-section causes the neutral line to change. Chunyu Fu et al (2018) [13] concluded that the presence of cracks causes a nonlinear stress distribution along the beam cross-section, which changes the neutral axis of the cross-section and further affects the stiffness of the beam. Figure 21 shows that the stiffness of the BRC beam cross-section decreases from the initial crack until the beam collapses.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term displacement is generally calculated using the effective moment of inertia across the span at the service load [12]. Chunyu Fu (2018) [13] presents a method of estimating the stiffness of cracked beams based on the stress distribution. In his conclusion, he said that the presence of cracks causes a nonlinear stress distribution along the beam section, which changes the neutral axis of the cross-section and further affects the stiffness of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the continuity of deflections, bending moment and shear force at each of the cracked cross-sections are required while the slope jump is allowed [6]. The theory of fracture mechanics is utilized to link the rotational stiffness of the spring to the size and geometry of a crack [7]. The discrete spring model was adopted by Wang et al [8] to analytically investigate the buckling of internally weaken columns.…”
Section: Introductionmentioning
confidence: 99%
“…Although open cross-section beams are often used in engineering structures, there are few studies that address the detection of cracks by vibration analysis for these types of structural elements, see for instance [15]. The intention of the authors is to investigate the behavior of I-beams with longitudinal cracks by involving numerical methods since these have been proved as reliable and versatile [16].…”
Section: Introductionmentioning
confidence: 99%